A Simple and Green Protocol for the Synthesis of 3,4-dihydropyrimidin-2(1H)-ones Using 11-Molybdo-1-vanado phosphoric Acid as a Catalyst Under Ultrasound Irradiation - Laxmikant D. Chavan; Surekha N. Deshmukh; Sunil G. Shankarwar (Orbital: The Electronic Journal of Chemistry, 2019)
A one-pot three-component reaction of ethyl acetoacetate, aldehydes and urea has efficiently been carried out in the presence of 11-molybdo-1-vanadophosphoric acid in ethanol at room temperature under ultrasound irradiation to form the corresponding 3,4-dihydropyrimidin 2(1H)-ones in high yields. The 11-molybdo-1-vanadophosphoric acid (H4PMo11V1O40) was prepared and characterized by FT-IR spectroscopy, TG-DTA analysis and XRD analysis techniques. The presence of Keggin structure and incorporation of vanadium into the Keggin structure of synthesized H4PMo11V1O40 catalyst was confirmed by FT-IR and powder XRD analysis techniques. TG-DTA analysis results indicated that H4PMo11V1O40 catalyst was thermally stable up to the temperature 434 °C. The present catalytic system is recyclable and can be reused without greater loss of reactivity.DOI: http://dx.doi.org/10.17807/orbital.v11i5.1423